Criminal Law Education: Preventing Online Fraud and Cybercrime in Ngalang Village, Gedangsari Sub-district, Gunungkidul, Yogyakarta - Aryono Aryono; Ramlin Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The rapid development of digital technology has significantly expanded public access to internet-based services; however, it has simultaneously increased exposure to cybercrime risks, particularly online fraud, which is increasingly affecting rural communities. This community service program aims to enhance legal and digital literacy among residents in preventing cybercrime in Ngalang Village, Gedangsari Sub-district, Gunungkidul Regency. The program employs a participatory-educational approach, incorporating legal awareness sessions, interactive discussions based on real case studies, simulations for identifying cybercrime patterns, and practical training on preventive measures and reporting mechanisms. Evaluation was conducted using pre-test and post-test instruments to assess participants’ level of understanding. The results indicate a significant improvement in legal literacy and participants’ ability to recognize and anticipate various forms of online fraud and cybercrime. These findings demonstrate that community-based legal education is an effective preventive strategy in addressing digital crime. Accordingly, this program contributes to strengthening legal awareness and enhancing the resilience of rural communities against cyber threats in the digital era.